Evaluation of New Biomarkers in the Prediction of Malignant Mesothelioma in Subjects with Environmental Asbestos Exposure - Demir, Melike; Kaya, Halide; Taylan, Mahsuk; Ekinci, Aysun; Yılmaz, Sureyya; Teke, Fatma; Sezgi, Cengizhan; Tanrikulu, Abdullah Cetin; Meteroglu, Fatih; Senyigit, Abdurrahman (Lung, 2016)
Introduction The purpose of this study was to investigate the potential value of certain biomarkers in predicting the presence of malignant pleural mesothelioma (MPM) in individuals environmentally exposed to asbestos. Methods This prospective study investigated three groups; a control group composed of 41 healthy subjects, an asbestos exposure group consisting of 48 individuals, and a MPM group consisting of 42 patients. Serum levels of soluble mesothelin-related peptide (SMRP), thioredoxin-1 (TRX), epidermal growth factor receptor (EGFR), fibulin-3, syndecan-1 (SDC-1), and mesothelin were determined. Results Benign pleural plaques were present in 27 (58.3 %) of the individuals in the asbestos exposure group. The asbestos exposure group had significantly higher mean TRX, SMRP, and mesothelin levels compared to the control group ( p = 0.023, p = 0.011, and p < 0.001, respectively). Compared to the asbestos exposure group, the MPM group had significantly higher mean EGFR, TRX, SMRP, and fibulin-3 levels ( p = 0.041, p = 0.023, p = 0.002, and p = 0.001, respectively), and significantly lower mean SDC-1 levels ( p = 0.002). Unlike the other biomarkers, SMRP and TRX levels increased in a graded fashion among the control, asbestos exposure, and MPM groups, respectively. Area under the curve values for SMRP and TRX were 0.86 and 0.72, respectively (95 % CI 0.79–0.92 and p < 0.001 for SMRP, and 95 % CI 0.62–0.81 and p < 0.001 for TRX). The cut-off value for SMRP was 0.62 nmol/l (sensitivity: 97.6 %, specificity: 68.9 %, positive predictive value (PPV): 56.2 %, and negative predictive value (NPV): 98.3 %) and for TRX was 156.67 ng/ml (sensitivity: 92.9 %, specificity: 77.6 %, PPV: 41.4 %, and NPV: 92.1 %). The combination of the biomarkers reached a sensitivity of 100 %, but had lower specificity (as high as 27.7 %). Conclusions Serum biomarkers may be helpful for early diagnosis of MPM in asbestos-exposed cases. SMRP and TRX increased in a graded fashion from the controls to asbestos exposure and MPM groups. These two seem to be the most valuable biomarkers for the diagnosis of MPM, both individually and in combination.